Ketahanan 22 Genotipe Cabai (Capsicum spp.) terhadap Phytophthora capsici Leonian dan Keragaman Genetiknya - Rahmi Yunianti; Sarsidi Sastrosumarjo; Sriani Sujiprihati; Memen Surahman; Sri Hendrastuti Hidayat (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
Laboratory and field experiments were carried out to analyze genetic diversity of 22 pepper genotypes (Capsicum spp.) and their resistance to Phytophthora capsici Leonian. Resistance screening was performed in plastic flats 72 cells. Inoculation was done on 28-day old pepper plant soon after watering by pipeting 5 ml of inoculum (105 zoospore/ml) at the base of each plant. P. capsici  isolate used in this experiment was TG01, identified as race 3 based on AVRDC differential pepper lines (PI 188478, PBC 602, PBC 137 and Early Calwonder).  The evaluation of pepper genotypes characteristic was conducted in the field.  Principle Component Analysis, Clustering Analysis and Biplot Analysis were used to analyze genetic diversity based on 37 characters. Result of resistance evaluation showed that two genotypes (C4 and C13) were identified as resistant, 7 genotypes (C2, C3, C5, C8, C10, C15, and C20) as slightly resistant, 6 genotypes (C7, C9, C17, C19, C21 and C27) as slightly susceptible, and 7 genotypes (C1, C11, C18, C28, C48, C64, and C65) as susceptible.  Based on genetic diversity analyzed, all genotypes could be divided into 4 clusters.  Cluster I consisted of 18 genotypes i.e. C1, C2, C3, C4, C5, C7, C8, C9, C10, C13, C14, C15, C17, C18, C19, C28, C64, and C65. Cluster II consisted of only 1 genotype i.e. C48.  Cluster III consisted of 2 genotypes (C20 and C21) which were characterized by the colour of corolla, corolla spot, and filament. Cluster IV consisted of 1 genotype (C27) which was characterized by fruit cross-sectional corrugation.   Key words :  Capsicum, resistance, Phytophthora capsici, genetic diversity, clustering.